BogaPreneur Lab: a web-based learning platform for culinary startup simulation in vocational schools - Fitriyana Fitriyana; Isnandar Isnandar; Syarif Suhartadi (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study aims to develop a web-based BogaPreneur Lab learning medium focused on culinary startup simulations for vocational high schools (SMK). The study employs a Research and Development (R&D) approach, involving two expert validators and 30 tenth-grade students in the Culinary Arts program as participants in a limited pilot test. Data collection was conducted using a Likert-scale questionnaire covering aspects of content, media, design, and student responses. The data were analyzed using quantitative descriptive methods to determine the feasibility level of the developed product. The results indicate that the learning media received a “very good” rating for content (85.7%) and media (81.25%), and a “good” rating for design (78.67%). The limited pilot test results showed a student response rate of 79% in the “good” category, with the highest scores in the appearance and content quality aspects. However, the ease of use and learning motivation aspects still need improvement. Overall, BogaPreneur Lab is deemed suitable for use as an innovative web-based learning medium to support culinary entrepreneurship education in vocational high schools.